Alveolar Bone Biology in Extrusion Splint Technique - Sharma, P; Shankar, TP (Kathmandu University Medical Journal, 2013)
The moment after the tooth avulsion, blood supply to the pulp is interrupted and the periodontal ligament cells are exposed to injury from the external environment. Complete healing is possible if the tooth can be immediately replanted and favorable environment is created .A case of report of intruded and mobile upper left central incisor due to Road Traffic Accident of a twenty-two-year-old patient is presented here. In which, intentional extrusion traumatized tooth and then flexible acrylic wire splinting was done to stabilize it. Previously there was no periapical bone support but with nine months maintenance follow up bone has shown a significant improvement towards healing. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 66-69 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8023